455 Obesity modifies the effect of 4 months of CPAP on glucose levels in adults with obstructive sleep apnea. (3rd May 2021) - Pak, Victoria; Maislin, David; Keenan, Brendan; Townsend, Raymond; Benediktsdottir, Bryndis; Guo, Xiaofeng; Pack, Allan; Gislason, Thorarinn; Kuna, Samuel
Abstract: Introduction: Continuous positive airway pressure (CPAP) therapy may improve insulin sensitivity and glucose tolerance seen in individuals with obstructive sleep apnea (OSA), however there is a lack of studies on whether obesity modifies the effect. We examined the baseline and follow-up levels of insulin and glucose following 4 months of CPAP treatment among participants with body mass index (BMI) <30, 30≤ BMI<35, and BMI≥35 kg/m2. Methods: We identified 221 adults (84% males) with newly diagnosed OSA in the Penn Icelandic Sleep Apnea (PISA) Study, with a mean (±SD) BMI 31.7 +- 4.2 kg/m2 and apnea-hypopnea index (AHI) of 35.7+-15.6 events/hour. Associations between changes in natural log of the biomarkers within BMI groups were explored, controlling for a priori baseline covariates of age, baseline BMI, race, sex, site, and current smoking status. Results: The mean proportional change (from baseline to follow-up) in log-transformed glucose in CPAP adherent participants was significantly larger in the BMI ≥35 and 30≤ BMI<35 groups compared to BMI <30. Within the BMI ≥35 group, the baseline to follow up increase in glucose post-CPAP was 1.08 (95% CI 1.01–1.15), while there were no significant changes in the other 2 BMI groups. A mediation analysis was performed with models including BMI change, and glucose was found to be significantly different between groups. There was no statistically significant association for insulin. Conclusion: Our findings show that obesity modifies the effect of four months of CPAP on glucose levels. Support (if any): 1P01-1HL094307